US–China trade war and the WTO dispute settlement mechanism. Issue 3 (15th November 2019) - Adekola, Tolulope Anthony
Abstract : Purpose: The paper is prompted by the US–China trade war and its implications for the sustenance of the multilateral trading system. The two rivals resorted to "self-help" without recourse to the World Trade Organization (WTO) dispute settlement system, flouting the WTO as an adjudicator in trade disputes. This paper aims to analyze the drawbacks in the settlement system and examines the urgent need for a retroactive remedy. Design/methodology/approach: This paper adopts desk-review and jurisprudential analysis of the relevant rulings of the WTO dispute settlement body. Using desk-review, primary sources such as the relevant domestic legislations invoked by the USA and China to trigger the trade war were discussed and critically analyzed. Findings: This paper finds that the unilateral and protectionist actions that characterize the trade war can be linked to the loss of confidence in WTO remedies to redress members' retroactive economic losses. This finding is useful in arguing for the incorporation of a retrospective monetary remedy to forestall the reoccurrence of a similar trade war and save the WTO from being dysfunctional. Originality/value: Although, whether there should be retroactive remedies in the settlement system has been long debated, this paper makes a significant contribution by highlighting why the drawbacks in the settlement system have become so prominent in the context of this trade war. This paper strengthens the urgent need for WTO dispute settlement reform to prevent a reoccurrence of another global distortion of trade.